Bimetallic Ni–Co‐based metal–organic framework: An open metal site adsorbent for enhancing CO2 capture. (26th May 2019) - Abdoli, Yekta; Razavian, Marjan; Fatemi, Shohreh
Abstract : An open metal site framework named UTSA‐16 was synthesized and modified as a high‐capacity adsorbent for reversible CO2 capture. Partial substitution of intrinsic Co 2+ sites of UTSA‐16 with Ni 2+ centres was realized in the molar composition range 0–75% Ni with the aim of increasing CO2 uptake. Synthesized bimetallic Ni x ‐UTSA‐16 ( x  = 0, 20, 50, 75) materials were characterized using various techniques to assess the influence of chemical composition on CO2 binding affinity and any subsequent physical change in morphology, crystal size and porosity on the total uptake. Experimental isotherm adsorption studies showed the following trend for CO2 adsorption capacity employing the Ni x ‐UTSA‐16 series: Ni20‐UTSA‐16 > UTSA‐16 > Ni50‐UTSA‐16 > Ni75‐UTSA‐16. According to the dynamic breakthrough CO2 profiles measured for a mixture of CO2 and CH4 (15/85 molar ratio), Ni20‐UTSA‐16 exhibited 2 times the breakthrough time with 1.5 times the loading capacity at 75 Nml min −1 feed flow rate, compared to the parent UTSA‐16. In addition, the Ni20‐UTSA‐16 bimetallic metal–organic framework exhibited lower isosteric heat of adsorption compared to UTSA‐16 (Δ H ave  = 28.54 versus 46.85 kJ mol −1 ). As a result, more than 95% of its capacity was restored by applying a partial vacuum for only 1 h at room temperature without involving any other time‐ and energy‐consuming regenerative step. Abstract : Synthesizing a mixed‐metal Ni‐Co MOF for selective separation of CO2 /CH4 breakthrough curves of CO2 from CH4 mixture has shown reliability of this adsorbent Adsorption‐desorption experiments has shown simple and fast condition for regeneration.